2017
DOI: 10.4244/eij-d-16-00776
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and clinical course of cerebral embolism in patients undergoing transcatheter left atrial appendage closure

Abstract: New cerebral embolic events occur after transcatheter closure of the left atrial appendage. However, most of the lesions demonstrate no gliotic transformation at follow-up. In all patients, the cerebral lesions were clinically unapparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Interestingly, the results of the follow‐up data from our study and the study from Majunke et al were similar. Majunke et al detected gliotic lesions in 3/9 (33%) patients at the 45‐day follow‐up , and our study showed a persistently positive FLAIR sequence in 2/7 patients (29%) at the three‐month follow‐up. It will be interesting to see the long‐term follow‐up results of larger studies.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Interestingly, the results of the follow‐up data from our study and the study from Majunke et al were similar. Majunke et al detected gliotic lesions in 3/9 (33%) patients at the 45‐day follow‐up , and our study showed a persistently positive FLAIR sequence in 2/7 patients (29%) at the three‐month follow‐up. It will be interesting to see the long‐term follow‐up results of larger studies.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, the data on long‐term follow up of ABLs after LAAC is sparse. Laible et al did not provide long‐term follow up in their study , whereas Majunke et al reported on one (3.6%) new lesion at the 45‐day follow‐up after LAAC . Therefore, our study is the first to provide categorical long‐term follow at three months after LAAC of MRI detected ABLs as well as neurocognitive testing and neurological examination.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations